Driving the enterprise to sustainable excellence : a Shingo process overview - Plenert, Gerhard Johannes (Boca Raton, FL : Routledge, Taylor & Francis Group, A Productivity Press Book, 2021)
This book presents a big-picture overview of the entire Shingo improvement process. It fully discusses the needs and benefits of the Shingo process, and what is required if you seek to execute the Shingo Model in your enterprise and focuses on creating an enduring organization-wide continuous improvement process. It gives the reader a discussion of the entire Shingo experience while the most existing books on the model are course specific. There are numerous discussions, conference talks, and webinars of why the Shingo process is beneficial, and what types of improvements can be achieved, but the crucial material has not been assembled in one concise book, giving the executive, manger, or supervisor an overview and understanding of what the Shingo experience entails. The main purpose of this book. It is for the executives who want to understand their role in supporting and leading middle management with its implementation. Many executives from developing countries all over the world are seeking a concise definition of what the Shingo model is, and this book functions as the perfect primer. Even those who have attended and implemented the lessons from the Shingo Institute's courses would find this book a benefit as it serves perfectly as backup and reference material. In addition, this book helps anyone who has started their journey with the Shingo model and may be confused about what to do and expect -- It gives them a vision of what the continuing journey will look like. The Shingo process is being taught at numerous universities and this book could indeed serve as the appropriate textbook or supplemental reading. Essentially, this book teaches an innovative and extremely successful approach to continuous improvement, referred to as the Shingo process. It is based on a set of universally accepted principles that are endorsed by improvement leaders such as Covey and companies such as Toyota. This book is not a detailed review or a replacement of the Shingo workshops. It is an overview of the entire Shingo process, starting with a discussion of the challenges that many of todays enterprises are experiencing. The author, in his role as a PhD in economics, has studied industries and has worked closely with many of them attempting to understand their weaknesses. Next, this book builds upon an understanding of these weaknesses. The book discusses how the over-all Shingo methodology fits into these organizations and highlights the benefits. The next step is then to discuss what requirements are necessary for an organization to get ready for a Shingo transformation. What are the steps that the organization needs to go through, and when will it know that it is ready to begin? The book briefly reviews the Shingo Insights and Principles and explains how the Shingo courses should be best utilized to facilitate the desired transformation. It suggests some alternative plans for over-all implementation based on the current state of the enterprise. It explains why there is no one way for successful implementation and how the implementation sequence needs to be customized. It also discusses the length of time needed for success and how this differs depending on the current enterprise environment. Lastly the book explains how the implementation and Shingo training is never finished. It is an on-going process and success is defined by internal improvements, not by some arbitrary external benchmark. The book is intended to be educational, thought provoking, entertaining in its stories and examples, and a guideline towards the development of a plan for continuous improvement. This book is filled with stories and examples, showing successful and not so successful implementations. The stories are used to highlight many of the pitfalls that have arisen and may arise for you and which can be avoided if the reader is aware of them and knows how to watch for them.
OCLC-licensed vendor bibliographic record.
Keywords: Total quality management; Continuous improvement process; Organizational effectiveness; Organizational change; BUSINESS & ECONOMICS / Production & Operations Management; BUSINESS & ECONOMICS / Leadership; BUSINESS & ECONOMICS / Strategic Planning